2016
DOI: 10.15171/jlms.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Changes in Human Dentin after Ablative and Subablative Er:YAG Laser Irradiation

Abstract: Introduction: This study investigated the influence of Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) laser on microhardness, chemical composition and subsurface morphology of dentin cavity walls. Methods: Forty sound human premolars were selected and randomly assigned into four groups. Class V cavities were prepared either with an Er:YAG laser (groups 1 and 2; 15 Hz, 250 mJ for enamel, 10 Hz, 200 mJ for dentin) or with a high speed handpiece (groups 3 and 4). The specimens in groups 1 and 3 served as the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
2
12
0
1
Order By: Relevance
“…33 In this study, the microhardness value and thus the rate of remineralization using the Erbium YAG laser in all groups were significantly higher than the control group. This result is consistent with studies by Moosavi et al 13 and Hossain et al 34 Perito et al also reported secondary caries that occurred less frequently in laser-prepared cavities compared with a bur. 35 Ana et al pointed to the increased resistance of enamel and dentin using the Erbium laser in the treatment of dental caries.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…33 In this study, the microhardness value and thus the rate of remineralization using the Erbium YAG laser in all groups were significantly higher than the control group. This result is consistent with studies by Moosavi et al 13 and Hossain et al 34 Perito et al also reported secondary caries that occurred less frequently in laser-prepared cavities compared with a bur. 35 Ana et al pointed to the increased resistance of enamel and dentin using the Erbium laser in the treatment of dental caries.…”
Section: Discussionsupporting
confidence: 92%
“…The FESEM examination showed that the partial dentinal tubule occlusion was observed with sub-mineral materials in each of the groups of bioactive glass, glass ionomer and the laser compared to the control group, in line with Saffarpour et al 19 and Moosavi et al 13 The results obtained in this study had an experimental nature, as it may be better to carry out this study on the basis of clinical design to determine whether the results of this study are in agreement with the clinic. It is recommended that a variety of different lasers and liners should be investigated on the affected dentin in future studies in order to scrutinize closely which of the cases would increase the dentin mineralization, particularly in the case of a laser whose results in this test are promising.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Mechanisms such as connection due to melting and strength of enamel crystals, the reduction of water and enamel carbonate, an increase in hydroxyl ions, and changes in the structure of enamel proteins are theories that explain the increased resistance of teeth against acid in laser irradiation. [15][16][17] High-power lasers such as Er: YAG lasers can induce cracks in the enamel. It can also roughen the enamel surface, which can make the tooth more susceptible to decay.…”
Section: Discussionmentioning
confidence: 99%